Analisis Pola Fungsi Kalimat pada Teks “Kepala Suku Len” Buku Bahasa Indonesia SD/MI Kelas IV - Tsurayya, Nabilah Salma; Nugraheni, Aninditya Sri; Isma Nadia Mumtaz, Isma Nadia Mumtaz Isma Nadia Mumtaz (Faculty of Teacher Training and Education of Undaris, 2025)
This study aims to analyze the sentence function patterns in the text “Kepala Suku Len” containedin the Indonesian language textbook Bahasa Indonesia: Lihat Sekitar! for Grade IV SD/MI (MerdekaCurriculum edition). The study stems from the urgency of understanding syntactic structures in children'sreading texts, particularly in the context of text-based learning that emphasizes language skills and criticalthinking. A descriptive qualitative approach was employed using content and syntactic analysis techniques.Data were obtained through documentation of sentences in the text, which were then analyzed based ontraditional and functional syntactic theories. The results show that the text is dominated by S-P (Subject–Predicate) and S-P-K (Subject–Predicate–Complement) sentence patterns, along with variations such as S-P-O, S-P-O-K, and K-S-P. These patterns indicate a tendency toward simple yet communicative sentencestructures that support the reinforcement of social and moral values. These findings suggest that the readingtext in the textbook conforms to syntactic rules and is relevant for the development of language competenceand literacy among elementary school students. This study is expected to contribute to the development ofmore functional, communicative, and learner-appropriate teaching materials.Keywords: children's reading text, Merdeka Curriculum, syntax, sentence function pattern, textbook